Patterns of use of medicinal plants in Chocó and Cauca (Colombia) (2020)
In total, 1178 records were obtained on the use of medicinal plants; 902 for the department of Chocó and 276 for the department of Cauca. Useful in the treatment of 130 different diseases or ailments, associated with 17 medicinal categories product of the literature review of 17 publica- tions. 766 species of vascular plants were found of which 392 sp. for Chocó and 374sp. for Cauca, grouped into 132 families. The most representative families in the Chocó are: Gesneriaceae (103 uses), Asteraceae (83), Piperaceae (65), Arecaceae (46) and Araceae (41). In Cauca, the following stand out: Piperaceae (132 uses), Asteraceae (127), Fabaceae (68) Arecaceae (66), Gesneriaceae (51). The health problems with the highest number of treatments in Chocó were snake bites (194 use records), malaria (100), fever (74), liver disorders and disorders (74) and headache (62), while, in Cauca were snake bite (209), skin wounds with (77), diarrhea (58), fever (58) and kid- ney disorders and disorders (41). Regarding human groups, Afro-Colombians obtained the high- est number of records, followed by indigenous and mestizos.